As we saw them the first Japanese Embassy to the United States - Miyoshi, Masao (New York Kodansha International, 1994)
The story of the first Japanese diplomatic mission to the US. This volume takes a look at cross-cultural relationships and at the roots of intolerance.--Provided by publisher.
Includes bibliographical references (pages 209-225) and index.
Keywords: Man'en Gannen Kenbei Shisetsu (Japan); United States -- Relations -- Japan; Japan -- Relations -- United States; Japan -- Foreign relations -- To 1868.